PERBEDAAN PEMILIHAN MAKANAN DAN FAKTOR YANG BERKAITAN PADA REMAJA PUTRI DI SMA DAERAH KOTA DAN KABUPATEN - Faradila, Ovi Eka; Kuswari, Mury; Gifari, Nazhif (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2019)
This study was aimed to analyze differences in food selection and factors related to adolescent girls in the urban and rural high schools. The sampling technique used is the sample size difference of 2 proportions. Data was collected by giving questionnaires to respondents which included food choices and its related factors such as social media, body image, nutritional knowledge, food labels, and peers. Body weight and height used to measure the anthropometric data. The statistical test used in this research was the t-test. There were no differences in food choices, use of social media, perception of actual body shape, perception of desired body shape, and perception of ideal body shape in urban and rural (p> 0,05). There were differences in actual body shape with BMI, nutritional knowledge, understanding food labels , and peer influence in rural and urban (p <0,05). Found differences in perceptions of actual body shape with BMI, nutritional knowledge, understanding food labels, and peer influence in urban and rural areas. There were no differences in food choices, but there were differences in factors related.